1995
DOI: 10.1002/path.1711770114
|View full text |Cite
|
Sign up to set email alerts
|

An infarct‐like myocardial lesion experimentally induced in wistar rats with Africanized bee venom

Abstract: There is evidence in the literature that death following a bee or wasp sting may result from cardiac involvement. This study describes acute cardiac lesions experimentally induced in Wistar Rats submitted to intravenous inoculation of Africanized bee venom (ABV) and killed 1, 4, and 24 h after inoculation. Significant increases in serum enzyme levels were detected; light microscopy showed necrosis of the myocardium; and enzyme histochemistry showed inactivation of enzymes in and around the areas of necrosis. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 28 publications
0
17
0
2
Order By: Relevance
“…The presence of different molecules in the venom, including phospholipase A2, hyaluronidase, melittin, apamine [37][38][39][40] , and, most recently, a serine protease-like protein studied by Lima et al 41 , may contribute to skin necrosis at the sting site. Such necrosis has frequently occurred and has been reported by most studies in Brazil [33][34][35][36][37][38][39][40][41][42][43][44][45] . The presence of rhabdomyolysis characterized by fiber eosinophilia, vacuolization, and absence of nuclei can be seen in Figure 1B.…”
Section: Anatomopathological Examinationmentioning
confidence: 99%
“…The presence of different molecules in the venom, including phospholipase A2, hyaluronidase, melittin, apamine [37][38][39][40] , and, most recently, a serine protease-like protein studied by Lima et al 41 , may contribute to skin necrosis at the sting site. Such necrosis has frequently occurred and has been reported by most studies in Brazil [33][34][35][36][37][38][39][40][41][42][43][44][45] . The presence of rhabdomyolysis characterized by fiber eosinophilia, vacuolization, and absence of nuclei can be seen in Figure 1B.…”
Section: Anatomopathological Examinationmentioning
confidence: 99%
“…Previous studies from our laboratory carried out on Wistar rats have demonstrated electrocardiographic (ECG) 2 and enzymatic 7 changes and morphological lesion of the AMI type 8 , showing a possible direct toxic action of the venom on cardiac muscle. Using monkey cardiomyocytes in culture 21 , it was demonstrated that previous treatment of bee venom with anti-melittin antibody eliminated the cardiotoxicity, suggesting that this lesion may be mainly due to melittin.…”
Section: Discussionmentioning
confidence: 98%
“…Several factors are hypothesized to participate in the pathogenesis of ATN: 1) a direct toxic effect of ABV on renal tubules, especially proximal tubules 12,23,24 ; 2) a toxic effect of myoglobin and hemoglobin on the tubules 7,24 ; 3) an ischemic effect mediated by AVB or by substances released in the organism, or by a fall in cardiac output due to AMI-like lesions 8 with a consequent fall in MAP reducing renal plasma flow, and 4) a stress-potentiating effect acting, for example, on NAD release in the myocardium 7 aggravating the cardiac ischemic component and consequently renal perfusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rarely, direct myocardial necrotizing effect of large amounts of venom released during multiple bee stings has also been postulated as a cause of myocardial damage. 2,4,5 Two variants of Kounis syndrome have been described. 4 Type I variant includes normal coronary arteries without predisposing factors for coronary artery disease and Type II variant includes patients with culprit but quiescent pre-existing …”
Section: S179mentioning
confidence: 99%